2021
DOI: 10.9778/cmajo.20200115
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outbreak among physicians at a Canadian curling bonspiel: a descriptive observational study

Abstract: C anada confirmed its first case of the novel coronavirus disease 2019 (COVID-19), a respiratory illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), on Jan. 25, 2020. 1 As of Dec. 7, 2020, there were more than 420 000 confirmed cases and nearly 13 000 deaths in Canada. 1 The World Health Organization (WHO) declared a global pandemic on Mar. 11, 2020, 2 which was also the date that physicians from around Canada gathered for a curling bonspiel in Edmonton (63rd Annual Western Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…and played a major role in participants contracting SARS-CoV-2 within the basketball stadium during the match. These findings correspond with other reports which have observed the transmission of SARS-CoV-2 during rigorous physical activity [15][16][17] in particular indoor activities 18,19 . Interestingly, a recent study carried out in the sport of rugby-which is not played indoors-has shown that there appears to be no risk of SARS-CoV-2 transmission 20 .…”
Section: Groupsupporting
confidence: 92%
“…and played a major role in participants contracting SARS-CoV-2 within the basketball stadium during the match. These findings correspond with other reports which have observed the transmission of SARS-CoV-2 during rigorous physical activity [15][16][17] in particular indoor activities 18,19 . Interestingly, a recent study carried out in the sport of rugby-which is not played indoors-has shown that there appears to be no risk of SARS-CoV-2 transmission 20 .…”
Section: Groupsupporting
confidence: 92%
“…In one study, 75% of the participants reported anosmia associated with loss or change in taste. In one confirmed case, anosmia was the only symptom (17). A cross-sectional survey study found that these symptoms are frequently reported in COVID-19 patients, and in most cases precede the onset of other symptoms (18).…”
Section: Discussionmentioning
confidence: 85%
“…The first case of COVID-19 in Canada was confirmed on January 25, 2020 ( Burak et al, 2021 ). On March 11, 2020, the World Health Organization (WHO) declared COVID-19 a pandemic; at this time, there were over 118,000 cases in over 110 countries and territories, and sustained risk of continued global spread ( Ducharme, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
“…The novel coronavirus 2019 (COVID-19) is a respiratory illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( Burak et al, 2021 ). SARS-CoV-2 was identified in December 2019.…”
Section: Introductionmentioning
confidence: 99%